Variability and Heritability of Morphological Traits in Collection of Cotton Genotypes (Gossypium hirsutum L.) and Their Potential Use for the Selection - Djaboutou, M. C.; Sinha, M.G.; Houedjissin, S.S.; Cacai, G.H.; Ahanhanzo, C. (European Scientific Journal, ESJ, 2017)
This study was conducted to estimate variability and heritability of some morphological traits available in 14 introduced cotton genotypes. The experiment was carried out in randomized complete block design with three replications. The experimental site is based in Cotton and Fibres Center for Agricultural Research at Cana located in the south of Republic of Benin.Analysis of variance showed highly significant differences among the 14 cotton genotypes (p˂0.001). The results showed high heritability for plant height, plant height to first fruiting branch, number of vegetative branches, length of vegetative branch, length of fruiting branch, number of fruiting branches and number of nodes among 14 varieties. Heritability values vary from 0.720 (NFB) to 0.999 (PH and LVB).Positive correlations were found between plant height and length of fruiting branch and number of fruiting branches and other morphological characters. A highly significant correlation (r = 0.80) was observed between plant height to first fruiting branch and plant height. The relatively high variability and heritability estimates for morphological traits suggested that they could be used in breeding programs.